Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.